2022
DOI: 10.1111/bjd.21767
|View full text |Cite
|
Sign up to set email alerts
|

Content validity of the Recap of atopic eczema (RECAP) instrument in Dutch, English and German to measure eczema control in young people with atopic eczema: a cognitive interview study

Abstract: and Laura Howells were involved in the original development of Recap of atopic eczema (RECAP). All three are members of the executive committee of the Harmonising Outcome Measures for Eczema (HOME) initiative. Laura Howells has acted as a consultant for the University of Oxford on an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The content validity of RECAP has also been assessed in various studies ( 19 – 21 , 28 , 29 ). The self-reported version of RECAP has been reported to be appropriate for use from the age of 12 years ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content validity of RECAP has also been assessed in various studies ( 19 – 21 , 28 , 29 ). The self-reported version of RECAP has been reported to be appropriate for use from the age of 12 years ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HOME VII meeting in 2019 recommended the use of the Atopic Dermatitis Control Test (ADCT) or RECAP as measures for long-term control as part of the core set of outcomes to be reported in all eczema trials (16,17). RECAP was developed and validated in English, but currently other language versions of RECAP such as German, Dutch, and Spanish versions were also considered comprehensible, and adults, as well as parents of affected children (19)(20)(21).…”
Section: Numerous Outcome Measures Have Been Developedmentioning
confidence: 99%
“…The 2 long-term eczema control instruments in the latter study showed strong correlation. Additionally, Gabes et al found the self-reported English, German, and Dutch RECAP relevant and comprehensible in young people from 12 years of age ( 13 ).…”
Section: Discussionmentioning
confidence: 99%